State Responsibility and Accountability Mechanisms in the Protection of Internally Displaced Persons under Contemporary International Law: The case of Cameroon - Gerard Tresor V Ngueumaga Kameni (European Scientific Journal, ESJ, 2026)
Internally displaced persons (IDPs) represent a growing global challenge occurring within the borders of sovereign States. Contemporary international law establishes that States hold primary responsibility for their protection; however, significant gaps remain between legal norms and practice. This article reassesses State responsibility for IDPs through a doctrinal and normative lens, examining international frameworks such as the Guiding Principles on Internal Displacement, the Kampala Convention, and relevant human rights and humanitarian law obligations. Using Cameroon as a case study, the article highlights persistent challenges, including selective compliance, weak domestic implementation, and limited accountability mechanisms. It argues that bridging these gaps requires stronger national legal frameworks and clearer international enforcement measures to ensure that States fulfill their duties to prevent displacement, protect affected populations, and provide durable solutions. By integrating doctrinal analysis with illustrative examples, the study clarifies how contemporary international law can effectively strengthen the protection of IDPs.